2015
DOI: 10.4028/www.scientific.net/kem.656-657.185
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Machining Damages Generated by a Piercing Process in CFRP Laminates

Abstract: This paper presents experimental examples of machining damages resulting from a piercing process in CFRP laminates. A circular perforation was formed in CFRP cross-ply specimen with a punch jig using different blade angles and two distinct dimensional conditions. Surface, cross-sectional, and internal changes to the CFRP specimens after the hole-punching were observed using optical microscopy and X-ray analysis to quantitatively evaluate damage, including delamination, around the perforation area. Results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…As a result, it was reported that a small clearance prevented extension of delamination and matrix cracks. 13 Among the studies discussing punching processes, Ueshiba et al 14 experimentally investigated the effects of punch blade, temperature, and clearance on the piercing-hole damage in thermosetting CFRP crossply laminates. Ogi 15 reported that the least amount of burrs, delamination and matrix cracks was generated when the clearance was 0.05 mm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it was reported that a small clearance prevented extension of delamination and matrix cracks. 13 Among the studies discussing punching processes, Ueshiba et al 14 experimentally investigated the effects of punch blade, temperature, and clearance on the piercing-hole damage in thermosetting CFRP crossply laminates. Ogi 15 reported that the least amount of burrs, delamination and matrix cracks was generated when the clearance was 0.05 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, studies on the effects of machining speed on the damage induced by punching and shear cutting were presented. Ueshiba et al 14 reported that, under quasi-static loading, indentation speeds in the range of 0.2-60 mm/s did not affect the machining quality such as burrs and delamination induced after punching. Similarly, Nakamura et al 9 and Yashiro et al 12 reported that indentation speeds in the range of 1-1000 mm/min did not affect the machining quality such as matrix cracks and delamination induced after shear cutting.…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al performed punching using a dual-stage puncher to reduce the punching load when a small clearance between the punch and the die was selected [8]. Nakamura et al and Ueshiba et al studied the effect of punch shape, clearance, and process temperature on the quality of the hole [9,10]. Klocke et al changed the cutting clearance, blank holder pressure, and cutting-edge radius to study the dimensional accuracy of the punched holes [11].…”
Section: Introductionmentioning
confidence: 99%
“…and Ueshiba et al. studied the effect of punch shape, clearance, and process temperature on the quality of the hole [ 9 , 10 ]. Klocke et al.…”
Section: Introductionmentioning
confidence: 99%